The effects of monetary policy on real estate investment in China: a regional perspective - Wei, Yigang; Lam, Patrick T. I.; Chiang, Yat Hung; Leung, Barbara Y. P. (International Journal of Strategic Property Management, 2014)
Monetary policy on real estate investment in China has had varying impacts across the country due to regional differences. A supply-determined model is used to measure the policy effects on property investment volume based on a set of regional data from 2003 to 2010. This research yields several important findings contributing to an understanding of uneven policy effects on the unbalanced regional markets. Firstly, it is revealed that the eastern coastal provinces in China have a higher dependence on bank loans for housing investment than that of the other inland provinces. Secondly, this research has disentangled the specific transmission channels of monetary policy in the property market. Bank loan supply, instead of interest rates, would be a potentially effective policy tool for the government in making property market adjustment. Thirdly, the eastern coastal provinces are more sensitive in their responses to the changes of monetary stances than the other non-coastal central and western provinces. Therefore, the government must take note of the significant heterogeneity arising from the regional differences in estimating the policy impacts, although monetary policy is uniformly employed in the nation most of the time. First Publish Online: 8 Dec 2014